2021
DOI: 10.3389/fcell.2021.771336
|View full text |Cite
|
Sign up to set email alerts
|

Wnt7b Inhibits Osteoclastogenesis via AKT Activation and Glucose Metabolic Rewiring

Abstract: The imbalance between bone formation and bone resorption causes osteoporosis, which leads to severe bone fractures. It is known that increases in osteoclast numbers and activities are the main reasons for increasing bone resorption. Although extensive studies have investigated the regulation of osteoclastogenesis of bone marrow macrophages (BMMs), new pharmacological avenues still need to be unveiled for clinical purpose. Wnt ligands have been widely demonstrated as stimulators of bone formation; however, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…146 Furthermore, increased Wnt levels in cells of the macrophage lineage markedly destroy osteoclast formation and activity, resulting in a rapid increase in bone mass. 146 The mechanism is that Wnt7b affects the process of glucose metabolism and the activation of AKT during osteoclastogenesis (Table 2). 146 Wnt7b is generally expressed by the osteogenic perichondrium, which benefits the development of long bones in mice, and the deletion of Wnt7b results in delayed osteogenesis in mouse embryos.…”
Section: Wnt7bmentioning
confidence: 99%
See 3 more Smart Citations
“…146 Furthermore, increased Wnt levels in cells of the macrophage lineage markedly destroy osteoclast formation and activity, resulting in a rapid increase in bone mass. 146 The mechanism is that Wnt7b affects the process of glucose metabolism and the activation of AKT during osteoclastogenesis (Table 2). 146 Wnt7b is generally expressed by the osteogenic perichondrium, which benefits the development of long bones in mice, and the deletion of Wnt7b results in delayed osteogenesis in mouse embryos.…”
Section: Wnt7bmentioning
confidence: 99%
“…146 The mechanism is that Wnt7b affects the process of glucose metabolism and the activation of AKT during osteoclastogenesis (Table 2). 146 Wnt7b is generally expressed by the osteogenic perichondrium, which benefits the development of long bones in mice, and the deletion of Wnt7b results in delayed osteogenesis in mouse embryos. 147,148 In contrast, the overexpression of Wnt7b in osteoblasts significantly promotes bone formation in mice.…”
Section: Wnt7bmentioning
confidence: 99%
See 2 more Smart Citations
“…Over the past decades, accumulated evidence has indicated that the activation of the Wnt signaling pathway is effective in enhancing bone defect healing through synergistic osteogenesis-angiogenesis regulation. Moreover, recent studies have shown that the Wnt pathway plays an indispensable role in osteoclastogenesis [ 17 , 18 ]. Specifically, Wnts can induce the expression of osteoprotegerin/osteoclastogenesis inhibitory factor (OPG/OCIF) on osteoblasts by modulating the differentiation of osteoclasts and influencing the function of osteoclasts, which also ultimately affects the bone resorption process [ 22 ].…”
Section: Introductionmentioning
confidence: 99%